Transverse vaginal septum presenting as secondary amenorrhoea: a rare clinical presentation - Yadav, Garima (BMJ Case Rep, 2020)
Transverse vaginal septum is one of the variants of Mullerian duct anomaly, caused as a result of defective fusion or recanalisation of vaginal and Mullerian organs. At an early age, it commonly presents as primary amenorrhea along with cyclical abdominal pain while later on usually it presents as dyspareunia and infertility. Our 22-year-old patient presented with secondary amenorrhea. It is very unusual for a transverse vaginal septum to cause secondary amenorrhea. MRI and clinical examination raised the suspicion of transverse vaginal septum causing secondary amenorrhea. She attained regular menstrual cycle after septum excision. The proposed theory behind it is obliteration of microperforated transverse vaginal septum because of menstrual blood and cell debris. Thus, a rare possibility of transverse vaginal septum should also be considered as a differential diagnosis of secondary amenorrhea.